Altitude differentially alters the force-velocity relationship after 3 weeks of power-oriented resistance training in elite judokas - Almeida, F.; Bonitch-Góngora, J.; Feriche, B.; Schoenfeld, B. J.; de la Fuente, B.; Padial, P. (European Journal of Sport Science, 2023)
This study investigated the effects of a 3-week power-oriented resistance training programme performed at moderate altitude on the lower-limb maximal theoretical power and force-velocity (F-V) imbalance of elite judokas. Twenty-two elite male judokas were randomly assigned to either a hypobaric hypoxia or normoxia group. Mechanical outputs from an incremental loaded countermovement jump test were assessed at sea level, before and after training, and 1 week later. Results indicated an increase in the maximal theoretical force and a reduction in the F-V imbalance both at moderate altitude and sea level. Altitude training induced additional benefits when compared to sea level for F-V imbalance (8.4%; CI: 0.3, 17.3%), maximal theoretical power (2.09 W·kg-1; CI: 0.13, 4.52 W·kg-1) and force (1.32 N·kg-1; CI: -0.12, 2.96 N·kg-1), jump height (3.24 cm; CI: 2.02, 4.80 cm) and optimal maximal theoretical force (1.61 N·kg-1; CI: 0.06, 3.60 N·kg-1) and velocity (0.08 m·s-1; CI: 0.00, 0.17 m·s-1) after the training period. The hypoxia group achieved their best results immediately after the training period, while the normoxia group achieved them one week later. These results suggest that a power-oriented resistance training programme carried out at moderate altitude accelerates and improves the gains in lower-limb muscle power, while minimizing lower-limb imbalances. Therefore, it seems appropriate to compete immediately after the return to sea level and/or use altitude training as a tool to improve muscle power levels of athletes without tapering goals, especially in highly trained power athletes, since their window of adaptation for further power enhancement is smaller.